(untitled) (INNOVATIVE ECONOMY, 2020)
Stasiv O.F., Kotko N.M., Mahas L.M. BASIC PRINCIPLES OF MODERNIZATION OF SOCIAL AND LABOUR RELATIONS IN THE CONTEXT OF REGULATION OF INCOMES OF RURAL POPULATION Purpose. The aim of the article is to carry out a study of the current state of social and labour relations on the basis of scientifically-grounded analysis of the most general indicators such as employment and unemployment, remuneration and living standards of rural population, and further modernization of social and labour relations in the context of regulating rural population incomes. Methodology of research. General scientific methods are used in the research, in particular: statistical, economic analysis – to determine the status and dynamics of such indicators as employment and unemployment, remuneration and living standards of the rural population; tabular – to organize the statistics. Findings. The problems of formation of the level of economic activity, employment and unemployment of the rural population of Ukraine and the Carpathian region are generalized, and the factors that significantly influence the formation of social and labour relations of the rural population are characterized. The following statements are established in the article, in particular: intensive processes of workforce dismissal by agricultural enterprises, narrowing the scope of work in rural areas cause a high level of informal employment of rural population, intensifying its migration behaviour, which, ultimately, leads to changes in the sphere of income generation. The analysis of modern and perspective directions of modernization of social and labour relations is carried out. Originality. A systematic approach is used to outline the problems and features of modernization of social and labour relations in the context of rural population income. Practical value. The obtained results will provide a scientific substantiation for the social and economic performance of the state measures taken to increase social standards, income and living standards of the rural population, and further develop social and labour relations. Key words: economically active population; employment; rural population; social and labour relations.